Chemical performance analysis of nanocellulose/boron-compound-reinforced hybrid UF resin - Yildirim M.; Candan Z.; Gönültaş, Oktay (ICE Publishing, 2021)
Urea-formaldehyde (UF) resin is the most important used adhesive in the production of wood-based composite panels, such as particleboard, medium-density fiberboard, oriented strand board and plywood. The aim of this work was to investigate the influence of nanocellulose, boric acid and borax on the chemical performance properties of UF resin. UF resin was reinforced with various loading levels of nanocellulose, boric acid and borax. Formaldehyde emission, gel time, solid content, viscosity, pH, specific gravity, shelf life and Fourier transform infrared spectra were evaluated as indicators of chemical performance. The findings showed that the formaldehyde emission of hybrid UF resin reinforced with nanocellulose/boron compounds decreased by up to 31.25%. The use of the reinforcement technique in the resin caused an increase in shelf life, viscosity and gel time but caused a reduction in the solid content of the resin. The apparent specific gravity of the resin was not influenced by the addition of nanocellulose/boron compounds. It was concluded that the chemical performance properties of UF resin could be enhanced by using proper nanocellulose, boric acid and borax loading levels. By using the reinforcement technique, it was possible to produce low-formaldehyde-emitting adhesives so that environmentally friendly products could be manufactured.
Keywords: adhesive; green chemistry; nanomaterials